Generation Z’s Resilience in The Workplace: A Systematic Literature Review - Sutanto Sutanto; Akbar Hidayatulloh; Nanang Suryadi (Journal of Social Research, 2026)
The transformation of the modern workplace has created increasing challenges for Generation Z workers, including digital disruption, career uncertainty, work-related pressure, and evolving organizational expectations. This study aims to systematically examine the development of research on Generation Z resilience in the workplace, identify dominant thematic clusters, explore the factors influencing resilience, analyze its impacts on psychological and workplace outcomes, and determine future research directions. This study employed a Systematic Literature Review (SLR) approach guided by the PRISMA framework. Relevant articles were collected from academic databases and analyzed using thematic synthesis and VOSviewer visualization to identify keyword networks, research clusters, and emerging trends. The findings reveal that resilience is a central concept strongly associated with stress, burnout, mental health, employee well-being, work engagement, mindfulness, emotional intelligence, and occupational health. The literature indicates that Generation Z workplace resilience is influenced by three major factors: individual resources (mindfulness, self-compassion, emotional intelligence, and grit), organizational support (respectful communication, leadership, and psychological safety climate), and workplace challenges (stress, insecurity, and workload intensity). Resilience contributes to reducing burnout and psychological distress while enhancing well-being, work engagement, and career adaptability. This study concludes that Generation Z workplace resilience is a multidimensional construct shaped by the interaction between personal capabilities and organizational environments. Future research should develop integrative theoretical models and apply longitudinal, qualitative, and mixed-method approaches to gain a deeper understanding of resilience development among Generation Z workers.